Intranasal delivery in glioblastoma treatment: prospective molecular treatment modalities. Issue 5 (May 2022) - Morales, Daniel E.; Mousa, Shaker
Abstract: Glioblastoma multiforme (GBM) is rare and fatal glioma with limited treatment options. Treatments provide minimal improvement in prognosis and only 6.8% of GBM patients have a life expectancy greater than five years. Surgical resection of this malignant glioma is difficult due to its highly invasive nature and follow-up radiotherapy with concomitant temozolomide, the currently approved standard of care, and will only extend the life of patients by a few months. It has been nearly two decades since the approval of temozolomide and there have been no clinically relevant major breakthroughs since, painting a dismal picture for patients with GBM. Although the future of GBM management seems bleak, there are many new treatment options on the horizon that propose methods of delivery to circumvent current limitations in the standard of care, i.e., the blood brain barrier and treatment resistance mechanisms. The nose is a highly accessible non-invasive route of delivery that has been incorporated into many investigational studies within the past five years and potentially paves the path to a brighter future for the management of GBM. Intranasal administration has its limitations however, as drugs can be degraded and/or fail to reach the site of action. This has prompted many studies for implementation of nanoparticle systems to overcome these limitations and to accurately deliver drugs to the site of action. This review highlights the advances in intranasal therapy delivery and impact of nanotechnology in the management of GBM and discusses potential treatment modalities that show promise for further investigation. Abstract : Intranasal, Glioblastoma, Nanotechnology, Blood brain barrier, Nanoparticles, Non-invasive.